2018
DOI: 10.1097/coc.0000000000000310
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Surgery Versus Chemotherapy for Recurrent Ovarian Cancer

Abstract: Objective The best course of treatment for recurrent ovarian cancer is uncertain. We sought to determine whether secondary cytoreductive surgery for first recurrence of ovarian cancer improves overall survival compared to other treatments. Methods We assessed survival using Surveillance, Epidemiology and End Results-Medicare data for advanced stage ovarian cancer cases diagnosed from January 1, 1997- December 31, 2007 with survival data through 2010 using multinomial propensity weighted finite mixture surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
1
16
0
4
Order By: Relevance
“…Роль хирургии в лечении пациенток с рецидивами рака яичников остается одним из наиболее спорных вопросов в онкогинекологии. В ряде ретроспективных и популяционных исследований было показано преимущество при проведении повторной циторедукции [1][2][3].…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Роль хирургии в лечении пациенток с рецидивами рака яичников остается одним из наиболее спорных вопросов в онкогинекологии. В ряде ретроспективных и популяционных исследований было показано преимущество при проведении повторной циторедукции [1][2][3].…”
Section: Introductionunclassified
“…По данным анализа результатов лечения 1635 пациенток из базы данных SEER, проведение хирургического лечения с последующей химиотерапией увеличивало медиану общей выживаемости (ОВ) на 1,3 года по сравнению с паллиативной химиотерапией [1]. Однако эти результаты не были подтверждены в рамках проспективных рандомизированных исследований.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The first report of secondary cytoreductive surgery was demonstrated by Dr. Berek in 1983 [3]. Then several retrospective studies and few prospective but non-randomized trials were reported [4567]. Four randomized trials were initiated in the 2010s and the patient recruitment lasted for a long period, ranging from 4.5–9.5 years [8].…”
mentioning
confidence: 99%
“…The rate of R0 increased from 39.4% (earlier pooled data) to 78.6% (recently closed trial) in non-selected or selected patients with recurrent ovarian cancer [25679]. Neither progression-free survival nor overall survival in GOG 213 was significantly improved in patients who underwent secondary cytoreductive surgery compared to chemotherapy alone [12].…”
mentioning
confidence: 99%